THE ELECTRIC FIELD STRENGTH INSIDE BARRIER LAYER OF POROUS ALUMINA DURING ANODIZING - S. K. Lazarouk; P. S. Katsuba; A. V. Andreenko; A. A. Leshok; A. A. Yakimchuk; V. B. Vysotskiy (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The electric field strength calculations inside porous alumina barrier layer during electrochemical anodizing in aqueous solutions of oxalic acid at a forming voltage of 90 to 250 V have been performed. The configuration of porous alumina cells with a porosity from 1 to 10 % have been used as the input data for calculations. It is found that the value of electric field strength inside porous alumina reaches 1010-1011 V/m. New phenomena and effects, appeared during alumina anodizing process with high forming voltages, have been analyzed.